Analisis Transparansi dan Akuntabilitas Pengelolaan Dana Bantuan Operasional Sekolah SMAN 7 Merangin Tahun 2021 - Ratih Kusumastuti; Mimi Sintia Nodera; Salman Jumaili (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of transparency and accountability on the management of school operational assistance funds at SMAN 7 Merangin in 2021. This research is a descriptive study with quantitative data analysis methods. This research uses purposive sampling technique. Research data collection is done by distributing questionnaires to 50 respondents. Data management using SPSS version 22 software. The test tools used in this study were descriptive statistics and multiple linear regression analysis. The results of this study indicate that: 1) Transparency and Accountability have a significant effect on the management of School Operational Assistance (SOA), 2) Transparency has a significant effect on the management of SOA, 3) Accountability has a significant effect on fund management SOA.